THE PSYCHOPEDAGOGIST’S WORK IN SCHOOLS: THE CONTRIBUTION OF PSYCHOPEDAGOGY IN BRAZILIAN INSTITUTIONS - Milane dos Santos Oliveira, Jaciara (Revista Gênero e Interdisciplinaridade, 2023)
The present work refers to the appreciation of Psychopedagogy within the school environment. It narrates the importance of the role of Psychopedagogy in identifying learning problems, which not always is observed by teachers or pedagogical coordination. In this work it is possible to detect the difficulties that the professional of the area faces inside the school for presenting a more sensitive and clinical look. This essay reports the historical path of Psychopedagogy in Brazil; it highlights an entire theoretical study about the psychopedagogical view within the school. The goal of the work is to understand the role of the Psychopedagogue within educational institutions; it aims knowing the path used by the precursors of Psychopedagogy within Brazil. This essay shows the value of Psychopedagogy within the school environment, in addition to reporting its entire course in Brazil, from the beginning to the present day. This aforementioned work will analyze the path taken by Psychopedagogy.